Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan pada Perum Damri Cabang Lampung - Muhammad Alfarobi; Desi Derina Yusda (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This research aims to determine the influence of the work environment and work discipline on employee performance at Perum Damri Lampung Branch. This research is associative with a quantitative approach using primary and secondary data. The sample was taken as many as 36 respondents with data collection techniques using questionnaires. The data analysis techniques used in this research are validity testing, reliability testing, multiple linear regression and hypotheses. The results of this research show that the work environment hypothesis has a significant effect on the performance of Perum Damri Lampung Branch employees. This is proven by t count > t table (5,000 > 2,034) with a significance of 0.000. Then the results of testing the work discipline hypothesis have a significant effect on the performance of Perum Damri Lampung Branch employees. This is proven by tcount > ttable (7,349 > 2,034) with a significance of 0.000. This shows that the more adequate the work environment and the higher the work discipline you have, the higher the performance will be.